OPTIMAL COST WIDE AREA MEASUREMENT SYSTEM AND VOLTAGE STABILITY PREDICTION IN POWER SYSTEM - Singh, Satyendra Pratap (IIT ( BHU ), Varanasi, 2017)
The foremost task for implementing the Wide Area Measurement System (WAMS) is determination of locations of Phasor Measurement Units (PMUs) in the power system in order to get desired measurements with least number of PMUs. The installation cost of PMUs is too high, therefore, it is uneconomical to install the PMUs at all the buses and make the system observable. Several algorithms and approaches have been reported in the literature for the optimal PMU placement (OPP) in power system. Such approaches can broadly be classified as conventional and evolutionary methods. The most of the reported methods pay attention to produce the optimal number of PMUs and their locations in the system. Some of the methods have included the full and maximum observability in the objective function. However, the observability may be altered if the locations of the PMUs are changed even if the optimal number remains same.
This Thesis submitted by IIT ( BHU ), Varanasi. PhD Scholar and Supervised by - S.P. Singh
Keywords: OPTIMAL; MEASUREMENT; VOLTAGE STABILITY; PREDICTION